Teaching Health Sciences at the Universidad de Antioquia, Colombia. - Osorio-Ramírez, Amantina; Gómez-Gómez, Margarita María; Alzate-Yepes, Teresita; Giraldo-Mejía, Gloria Eugenia; Salazar-Blanco, Olga Francisca (Revista Facultad de Medicina de la Universidad Nacional de Colombia)
Introduction: Studying the identity of university teachers contributes to the understanding of their professional career, since their personal and professional development is projected in their work, as well as in their commitment to educational change or improvement on the basis of the concept they have of themselves and their profession. Objective: To recognize the meanings of being a health science professor at the Universidad of Antioquia, Colombia. Materials and methods: Qualitative study, based on symbolic interactionism, carried out between 2016 and 2019. Semi-structured interviews were administered to 73 teachers who had been working for more than five years in the health sciences programs offered by the Universidad de Antioquia. Data were analyzed inductively and compared with each other until achieving the creation of an explanatory table that would allow addressing the objective of the work. Results: The meaning of being a health sciences professor at the Universidad de Antioquia was expressed as follows: 1) being a trainer: since professors conceived themselves as academics and educators; 2) having ethical behaviors: being a critical and caring counselor-companion for students who generates bonds with social responsibility; and 3) being someone welcoming: being a role model in terms of social relationships and demonstrating fulfillment with their performance in their teaching practice. Conclusion: Participants conceive teaching as a way to contribute to the development of critical thinking in students and define their role as facilitators of the students' learning process. Furthermore, they have a common interest, namely, to guide, support and facilitate such process, so that students acquire tools that allow them to achieve an appropriate personal and professional development in the affective, social, and life project dimensions.